Analisis Kemampuan Memimpin Pembelajaran Guru Penggerak Angkatan 4 Kabupaten Sikka - Agustina Elizabeth; Rambu Ririnsia Harra Hau (Departement of Mathematics Education, 2023)
Teachers in Sikka Regency contributed to the Driving Teacher Education Program Batch 4 according to the mandate of the Minister of Education and Culture in the Freedom to Learn Policy Episode 5. As teachers at LPTK we capture ideas and opportunities in following the dynamics of efforts to develop teacher competency so that it becomes a reflection in the learning process that liberates for graduates can become driving teachers. This study aims to analyze the ability of the driving teacher in leading learning that liberates students. This research was conducted using a field survey which was supplemented by questionnaires, observations, interviews, and documentation as a method of data collection. Data analysis uses data reduction, data triangulation, and data synthesis to parse conclusions. The results of the study show that prospective teacher mobilizers are able to lead learning in the process of driving teachers edication program.